Epidemiology of Coronavirus Disease 2019 at a County Jail—Alameda County, California, March 2020-March 2021. Issue 1 (January 2022) - Marusinec, Rachel; Brodie, Daniel; Buhain, Sonal; Chawla, Colleen; Corpuz, John; Diaz, Jennifer; Durbin, Michael; Moss, Nicholas; Okada, Reiko; Sanchez, Yesenia; Watkins-Tartt, Kimi; Yette, Emily; et al.
Abstract : Context: Coronavirus disease 2019 (COVID-19) incidence rates are 2- to 5-fold higher among persons incarcerated in the United States than in the general population. Program or Policy: We describe an outbreak investigation of COVID-19 at a jail (jail A) in Alameda County during March 2020-March 2021. Implementation: To prevent COVID-19 cases among incarcerated persons and employees, staff at jail A and the county public health department worked to develop and recommend infection control measures implemented by jail A including, but not limited to, face covering use among incarcerated persons and staff; cohorting incarcerated persons at a higher risk of severe COVID-19 in dedicated housing units; quarantining all newly detained individuals for 14 days; and offering testing for all symptomatic incarcerated persons, newly incarcerated persons at day 2 and day 10, and all persons who resided in a housing unit where a COVID-19 case was detected. Evaluation: A total of 571 COVID-19 cases were detected among incarcerated persons at jail A during March 2020-March 2021, which represented a total incidence of 280 per 1000 population, 5 times higher than the rate in Alameda County. Of the 571 cases among incarcerated persons, 557 (98%) were male; 415 (73%) were aged 18 to 40 years; 249 (44%) were Latino; and 180 (32%) were African American; 354 (62%) were not symptomatic; and 220 (39%) had no comorbidities. Less than 2% of infected incarcerated persons were hospitalized, and no deaths were reported. Discussion: COVID-19 disproportionately impacted persons incarcerated at jail A, with higher numbers among Latinos and African Americans. Implementation of COVID-19 infection control and testing measures, and collaboration between public health, law enforcement, and health care providers may have, in part, led to reductions in morbidity and mortality associated with COVID-19 at jail A.